Comparative study of chemical composition and evaluation of the In-Vitro antioxidant capacity of unripe and ripe banana species (Musa Sapientum) biowastes - Ibiyinka Ogunlade; Akinwumi Oluwafemi Akinmade; Adebayo O Ogunlade; Olugbenga Kayode Popoola (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2021)
The effort of developing countries in addressing zero hunger (Goal 2) with good health and well-being (Goal 3) of Sustainable Development Agenda requires a multi-disciplinary analytical approach to waste materials capable of decomposing through aerobic and anaerobic conditions. Hence a research on ripe and unripe banana peels as potential sources of nutrients, essential minerals and antioxidants was carried out using standard analytical techniques. The study revealed that the percentage moisture of the unripe and ripe banana peels ranged from 4.60 - 17.8; crude protein 1.94 - 2.73; fat 1.76 - 3.25; ash content 11.3 - 14.7; crude fibre 14.2 - 15.5; and carbohydrates 48.4 - 52.7. Mineral content showed significantly high levels of Na, K, Ca, Zn, Fe in unripe peels while that of ripe exhibited higher levels of Mn and P. Na/K for both ripe and unripe banana peels is less than 1 while Ca/P ranged from 1.63 - 2.64. The antioxidant capacity using 2, 2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH) assay ranged from 3.75 - 13.6 mg TE/g and total phenolic content in unripe and ripe banana peels ranged from 8.42 - 15.8 mg GAE/g with higher value in unripe peels. The results indicate that the peels can be utilized as sources of fibre, carbohydrate and essential minerals in fortification of animal feeds.